The paris library eaudiobook A novel. - Charles, Janet Skeslien (Simon & Schuster Audio, 2021)
An instant New York Times, Washington Post, and USA TODAY bestseller—based on the true story of the heroic librarians at the American Library in Paris during World War II— The Paris Library is a moving and unforgettable " ode to the importance of libraries, books, and the human connections we find within both" (Kristin Harmel , New York Times bestselling author). Paris, 1939: Young and ambitious Odile Souchet seems to have the perfect life with her handsome police officer beau and a dream job at the American Library in Paris. When the Nazis march into the city, Odile stands to lose everything she holds dear, including her beloved library. Together with her fellow librarians, Odile joins the Resistance with the best weapons she has: books. But when the war finally ends, instead of freedom, Odile tastes the bitter sting of unspeakable betrayal. Montana, 1983: Lily is a lonely teenager looking for adventure in small-town Montana. Her interest is piqued by her solitary, elderly neighbor. As Lily uncovers more about her neighbor's mysterious past, she finds that they share a love of language, the same longings, and the same intense jealousy, never suspecting that a dark secret from the past connects them. "A love letter to Paris, the power of books, and the beauty of intergenerational friendship" ( Booklist ), The Paris Library shows that extraordinary heroism can sometimes be found in the quietest places.